Vibration control of flexible rotors using a passive magnetic device working on the principle of electromagnetic shunt damping. (April 2023) - Vashisht, Rajiv Kumar
Abstract: Excessive rotor vibration can propagate the micro-cracks and hence the premature failure of the rotor system. A passive magnetic device working on the principle of electromagnetic shunt damping (EMSD) is proposed to passively control the rotor vibrations. Although, these EMSD-based damping systems are quite common in the literature, however, there is not even a single article available in the literature, showing the application of such a device passively controlling the rotor vibrations from a distance. Due to the flow of flux between the rotor, stator, and air gap, the modeling procedure for such an EMSD-based system changes completely and is not available in the literature. Due to rotor movement, there is a variation in the magnetic flux provided by the permanent magnets placed in the device. Due to electromagnetic interactions, electric currents are induced in the windings provided in the device. When these currents are allowed to pass through electrical resistance, damping forces are generated. In this way, vibration energy is converted into heat energy. In this research, it is observed that the damping effect is maximum for an optimal value of electrical resistance. The effect of several turns in the windings and permanent magnet thickness is also investigated in terms of the production of damping forces. The efficiency of the device is mathematically proved through simulations. Further, experimental results verify the effectiveness of the proposed device.